A profound mystery : the use of the Old Testament in Ephesians - Moritz, Thorsten. (Novum Testamentum, Supplements, 1996)
The primary focus of this study is the question of the extent and impact of Old Testament traditions in Ephesians. A close examination of the range of quotations, allusions and echoes found in the epistle shows that the Old Testament influence was greater and more deliberate than has hitherto been assumed. The main part of the book is a thorough exegetical study of various aspects of the question, ranging from identification of the relevant Old Testament texts to an examination of the ways in which they are appropriated and applied in the New Testament context. A number of implications emerge for our understanding of the letter's intended readership, and these are illuminating for the assessment of the epistle's relationship to the letter to the Colossians.